2016
DOI: 10.4103/2303-9027.183971
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cost-effectiveness between endoscopic ultrasound and endoscopic retrograde cholangiopancreatography in diagnosis of common bile duct stone in patients with predefined risks: A study from a developing country

Abstract: Background and Objectives:Endoscopic ultrasound (EUS) achieves results comparable to endoscopic retrograde cholangiopancreatography (ERCP) in the diagnosis of common bile duct (CBD) stone, but studies from the western have shown EUS to be less expensive in patients with intermediate risk for CBD stones. The aim of this study was to compare the costs of EUS and ERCP in the diagnosis of CBD stones in a developing country.Materials and Methods:A prospective study was done with 141 patients with suspected CBD ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In our study, we are observing the diagnostic accuracy of EUS versus ERCP which is the gold standard in detecting choledocholithiasis. In multiple studies, the majority of individuals reported a mean age of 55-59 years with the genetic predilection of disease directed towards male gender [ 11 , 12 ], while one study conducted in the same accord reported female gender to be more affected [ 10 ]. Majority of individuals presented with upper abdominal pain, jaundice, dilated CBD stones, acute or biliary pancreatitis, ultrasound or CT scan detections suggestive of stone [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we are observing the diagnostic accuracy of EUS versus ERCP which is the gold standard in detecting choledocholithiasis. In multiple studies, the majority of individuals reported a mean age of 55-59 years with the genetic predilection of disease directed towards male gender [ 11 , 12 ], while one study conducted in the same accord reported female gender to be more affected [ 10 ]. Majority of individuals presented with upper abdominal pain, jaundice, dilated CBD stones, acute or biliary pancreatitis, ultrasound or CT scan detections suggestive of stone [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, the majority of individuals reported a mean age of 55-59 years with the genetic predilection of disease directed towards male gender [ 11 , 12 ], while one study conducted in the same accord reported female gender to be more affected [ 10 ]. Majority of individuals presented with upper abdominal pain, jaundice, dilated CBD stones, acute or biliary pancreatitis, ultrasound or CT scan detections suggestive of stone [ 11 , 12 ]. The predominant category reported among sufferers of CBD stones was the intermediate-risk category [ 10 , 11 ], while in a study conducted in Taiwan, males suffered more than females and the majority of patients were categorized as high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Initial MRCP or EUS to triage patients for ERCP appears to be cost effective when compared with direct ERCP. 7,8 Although a recent study from the United Kingdom indicated that preoperative imaging with MRCP might be more cost effective than EUS, 9 the choice of test must be weighed carefully and may be determined by patient-specific factors. MRCP is noninvasive and may be favored in patients who are at above average risk for procedural sedation.…”
mentioning
confidence: 99%
“…Laparoscopic cholecystectomy is generally accepted as the gold standard treatment for symptomatic gallstones [1,2]. For patients who are not suitable operative candidates, endoscopic ultrasound (EUS)-guided cholecystoduodenostomy or cholecystogastrostomy can be performed using a double-flanged, fully covered, metal stent as a bridge to further transduodenal or transgastric cholecystolithotomy [3,4].…”
mentioning
confidence: 99%